The urban heat island (UHI) phenomenon in Cebu City, Philippines an initial study - Shih, Rowell Ray L.; Dy, Danilo T. (2014)
The Urban Heat Island (UHI) phenomenon is never considered an issue in urban planning for Cebu City, in spite of its rapidly increasing urbanization. This study tries to evaluate some factors that may contribute to the UHI phenomenon in Cebu City using the mobile transect method during the summer period. A thermometer measuring was mounted on a platform on top of a vehicle to measure the different temperatures of a given area in Cebu City. Preliminary results showed that presence of UHI phenomenon in Cebu City (ΔT=0.6॰C) and can still be considered moderate compared to other Asian cities. Among the many factors (i.e., temperature, humidity, elevation, distance to the shoreline and population), elevation was considered to be a significant predictor of the UHI phenomenon in Cebu City. Urban planning and provision of green spaces are essential in mitigating future heat stress likely to be experienced by people living in Cebu City.
Keywords: Urban heat island -- Cebu City